Histomorphological and correlative histophysiological studies on the gonadotrophs of Gaddi sheep - PARAMASIVAN, S; SHARMA, D N (The Indian Journal of Animal Reproduction, 2023)
Histomorphologial and histophysiological studies were correlative on gonadotrophs of Gaddi sheep.The folliculotrophs were oval (7.80-8.28 μm dia}, triangular or polygonal in shape. The number ofFSH-cells was231 ± 13 .8Q cells/mm2 in summer season. It increased considerably (330± 14.22 cells/mm2} during autumn season. Thepopulation of luteotrophs was also maximum during the autumn ( 446±22.45 cells/mm2} and minimum during summer(242± I 0.04 cells/mm2} seasons. The minimum diameter (8.04±0.13 μm) also occurred during summer season. Thedecreased size and population of the gonadotrophs during summer was correlated with the increased follicularatresia and decreased leuteinization of the follicles leading to anestrous (summer anoestrous). Increased populationwas associated with increased ovulation and leuteinization of the follicles during the autumn season when mostovulations occur.
Keywords: FSH; gonadotrophs; histomorphology; LH; sheep